Visual and Verbal Features of the Title Pages of News Pamphlets from 1570-1722 Concerning Executions at Tyburn - Luomala, Minna (My University, 2020)
This thesis is an examination of 51 early modern news pamphlets about executions at Tyburn, an execution site near London. The material dates from 1570-1722 and was gathered from Early English Books Online. The focus of the analysis is on the visual and verbal features of their title pages. The visual features cover the use of illustrations and other decorations, typography, and layout of the title pages. The verbal or linguistic features concentrate on textual labels, words that inform the reader about the form and content of a text. Headlines and topical labels that inform the reader about the topic of the text are also addressed to a lesser extent. Besides the analysis of the title pages, this thesis aims to present execution news as their own subgenre of sensationalist news and to shed light on the historical context and evolution of the genre. Previous studies on early modern news pamphlets have shown that a change from visually designed title pages to such that highlight verbal elements took place in the 1640s. The results of this thesis indicate that in execution pamphlets this change was more gradual, as some visually designed title pages still appear in the 1660s. Illustrations, often of a general type not directly depicting the contents but still related to executions, were commonly used on early title pages that had headlines or highlighted labels that did not clearly reveal the contents to tell of an execution. In the later material there appears an established set of frequently used textual labels that is partly shared with other news pamphlets and partly characteristic to execution pamphlets alone due to their relation to the execution process.
Keywords: Early Modern English, news pamphlets, genre, titles, title pages, illustrations, textual labels